"It Takes a Village": On UX Librarianship and Building UX Capacity in Libraries. Issue 2 (17th February 2017) - MacDonald, Craig M.
ABSTRACT: With growing interest in applying user experience (UX) methods to improve library interfaces, spaces, and services, it is critical to gain a deeper understanding of the organizational factors influencing libraries' adoption and incorporation of UX expertise. This article reports the results of semi-structured interviews with 16 UX librarians and focuses on how the positions were created, the benefits they have brought to their library, their biggest challenges, and the extent that their work is understood throughout the library. The article concludes with a preliminary model of library UX maturity and six critical directions for the future of UX librarianship.